Soil Chemical Properties and Agronomic Response of Sugarcane (Saccharum officinarum L.) Affected by Long Term No-Tillage Practice and Bagasse Mulch Application - Zaqyah, Irene; Niswati, Ainin; Evizal, Rusdi; Utomo, Muhajir (UNIVERSITY OF LAMPUNG, 2022)
Intensive tillage will continuously reduce soil quality, characterized by decreased soil organic-C. Low soil organic-C indicates the disturbance of soil fertility. More conservative soil management experiments have been done for seven years to restore the soil quality for sugarcane (Saccharum officinarum L.) productivity. This research aimed to study the effect of the tillage system, bagasse mulch, and their interactions on soil chemical properties and sugarcane agronomic response. The research was conducted on a Split Plot of five groups. The main plot was the tillage system consisting of intensive tillage and no-tillage, while the subplot was the bagasse mulch consisting of bagasse mulch and no-bagasse mulch. This study found that in sugarcane cultivation, no-tillage system was beneficial for soil P-available, sugarcane length, and sugarcane ripening; bagasse mulch was beneficial for soil organic-C and also soil P-available. The no-tillage system to increase P-available can be combined with bagasse mulch or no-bagasse mulch, but the no-tillage system combined with no-bagasse mulch increases the percentage of gap in sugarcane cultivation.